The community of the future (San Francisco : Jossey-Bass, 1998)
Trends shaping the evolution of community. The values of community. The impact of new communications technology. Creating communities in organizations. Strengthening the social fabric. Global dimensions of community.
Keywords: Community; Community life; Forecasting; Community; Community life; Forecasting